2020
DOI: 10.1177/0194599820959279
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of and Associations With Distress and Professional Burnout Among Otolaryngologists: Part II, Attending Physicians

Abstract: Objective To ascertain the prevalence of and associations with distress and professional burnout among academic otolaryngology attending physicians. Study Design Cross-sectional survey. Setting Twelve US academic otolaryngology programs. Methods A questionnaire was administered that encompassed sociodemographic and professional features, the Expanded Physician Well-being Index for distress, the 2-item Maslach Burnout Inventory for professional burnout, the Patient Health Questionnaire–2 screen for major depres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
(107 reference statements)
0
2
0
Order By: Relevance
“…Seven articles analyzed the impact of ACGME work hour restrictions on resident burnout and well‐being. The impact of ACGME work hour restrictions has been closely examined in many studies 10,14 ; several studies have specifically examined the impact of work hour restrictions on otolaryngology residents 10,13,15,16 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seven articles analyzed the impact of ACGME work hour restrictions on resident burnout and well‐being. The impact of ACGME work hour restrictions has been closely examined in many studies 10,14 ; several studies have specifically examined the impact of work hour restrictions on otolaryngology residents 10,13,15,16 …”
Section: Resultsmentioning
confidence: 99%
“…The impact of ACGME work hour restrictions has been closely examined in many studies 10,14 ; several studies have specifically examined the impact of work hour restrictions on otolaryngology residents. 10,13,15,16 In 2003, Baldwin et al 6 burden. 19 This study also found that 33% of PDs felt that the imposed work hour restrictions had a negative effect on patient care.…”
Section: Qualitative Analysis: Rates Of Otolaryngology Burnout Compar...mentioning
confidence: 99%